Memahami Kesia-sian dalam Kitab Pengkhotbah - Yohanes Krismantyo Susanta (Sekolah Tinggi Teologi Intheos Surakarta, 2017)
Abstract: This paper is an attempt to understand a phrase in the book of Ecclesiastes which is often-misunderstood that